Pengaruh Media Pembelajaran di Era Revolusi Industri 4.0 terhadap Hasil Belajar - Sukron Alrasyid IGB; Putri Susana Bela; Ferlian Nur Alif Prayoga; Meilisa Sajdah (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
The Industrial Revolution 4.0 has changed almost all aspects of human life, including education. One of the most notable changes is the shift in the use of learning media. Learning media is no longer just an additional tool but has become an important part in improving learning efficiency in our time. The impact of effective learning media in the era of the Industrial Revolution 4.0 reflects a fundamental paradigm shift in the way we learn and teach. The support of advanced technologies such as artificial intelligence, data analytics, virtual reality, and high-speed internet has opened the door to interactive, affordable, and personalized learning. Thus, researchers conducting this study aim to "Know the Influence of Learning Media in the Industrial Revolution Era 4.0 on Learning Outcomes" This research method was carried out using quantitative methods based on data conducted by researchers at MTs Plus Walisongo. This study uses Regression Test with several conditions, namely valid, reliable, and normally distributed data that produces learning media variables in the era of the industrial revolution 4.0 (X) has no effect on student learning outcomes variables (Y).